Effects of Physical Mutagen on Catalase Production - Salman Muhsan, Muhammad; Ahmed, Aneela; Khurshid, Shazia (Asian Journal of Chemistry, 2011)
The present study deals with the effects of physical mutagen on the production of catalse. The ultraviolet radiations were used as a physical mutagen. The effect of nitrous acid mutation on the catalase production was also observed. Some fermentation conditions such as fermentation period, concentration of substrate, pH, temperature, concentration of urea and KH2PO4 were optimized. It was resulted that activity of catalase from Aspergillus niger was maximum at 40 h of incubation, 8 % of glucose concentration (3.40 units/mg), at 30 ºC, at pH 7, at 0.2 % of urea concentration, at 0.4 % of KH2PO4. The mutation of nitrous acid decreased the catalase activity. Maximum activity of catalase after ultraviolet mutation, was found in mutant number 8 that was 5.983 unit/mg, which was exposed for 40 min under ultraviolet lamp.